Роль людського чинника у забезпеченні безпеки дорожнього руху - Гюлєв, Нізамі (Видавництво Львівської політехніки, 2015)
It is noted that traffic congestion is one of the main sources of elevated emotional intensity of the driver, on which depends the safety of road users. The negative impact of traffic congestion on the functional state of the driver and a changing his reaction in the time. Underlined the need to maintain the functional state of the driver in the normal range.
The role of human factor in providing road safety